Application of ultrafiltration membranes for purification and concentration of Sabin poliovirus type 1 - A. A. Kovpak; Yu. Yu. Ivin; A. N. Piniaeva; Yu. Kh. Khapchaev; S. V. Ozherelkov; A. V. Belyakova; A. A. Ishmukhametov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2021)
Introduction. Since the development of inactivated polio vaccines, different stages of the production process have been changed and improved. Current production of inactivated polio vaccines based on both wild and attenuated strains includes several technological stages, one of which is the concentration of the virus-containing liquid, which ensures poliovirus concentration, and purification of the virus-containing liquid from a significant part of the ballast components.Research objective is to compare the characteristics of ultrafiltration membranes and select the membranes that provide optimal value of purification and concentration of poliovirus type 1 (Sabin strain).Materials and methods. Laboratory ultrafiltration systems from two manufacturers with 50, 100, and 300 kDa membranes were used for the concentration. Results were evaluated by the content of total protein, which is the main stress for the subsequent purification stages, the value of infectious virus titer in the concentrate, and the content of D-antigen as the target product.Results and discussion. Obtained results demonstrated that the content of the target product (the highest D-antigen content) and purification from impurity proteins (the total protein content in the concentrate) were most optimal when a membrane with a cut-off of 300 kDa was used for concentration. The study also evaluated the real cut-off components by various membranes to determine the composition of the protein load on the target product.Conclusion. In terms of quality of the resulting target product and the manufacturability of the production process, the use of a 300 kDa membrane is the most appropriate when working out the technology for manufacturing inactivated polio vaccine based on Sabin strains of poliovirus and the Vero line as a producing culture.